a) -3 + 7 + 4 =
b) 1 + (-4) + (-6)
c) -10 + 20 + (-8)
poderiam me dizer como faz? por favor
Anexos:
![](https://pt-static.z-dn.net/files/d99/07f98e33572959b63c67dda4e7c6edf3.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
Explicação passo-a-passo:
a) -3 + 7 + 4 = +4 + 4 = + 8
b) 1 + (-4) + (-6) = 1 - 4 - 6 = -3 - 6 = - 9
c) -10 + 20 + (-8) = -10 +20 - 8 = +10 - 8 = +2
Perguntas interessantes
Matemática,
8 meses atrás
Física,
8 meses atrás
Geografia,
8 meses atrás
Matemática,
10 meses atrás
Geografia,
10 meses atrás
História,
1 ano atrás
História,
1 ano atrás